Determinantes da taxa básica de juros no Brasil: uma análise empírica no período de 2000 a 2011 - Schio, Thyago Américo (2013)
The existence and maintenance for long years of high domestic interest rate is a phenomenon sweeping the Brazilian economic environment. Although in recent years the domestic interest rate derated, Brazil still is characterized as one of the countries with higher interest rate in the world. In order to contribute to the discussion and understanding of the factors that allows the existence and maintenance for long years of high domestic interest rate, it is investigated the hypothesis that even if the internal interest rate is influenced by the foreign interest rate, there are endogenous mechanisms to the Brazilian economy that allow the reduction of the internal interest rate. Aiming objective responses, it is used a Vector Error Correction (VEC) compounded of six endogenous variables and an exogenous variable. As results, it follows that although there is a relationship between domestic and foreign interest rates, there is space for the economic policy, enabling a continuous reduction in the domestic interest rate.